2015
DOI: 10.1007/s12034-015-1047-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hydroxyapatite powder properties via heat treatment

Abstract: The properties of hydroxyaptite (HA) powder, especially its physical one, are largely influenced by the heat treatment process. Controlling of these changes is vital in deciding the suitability of applying this powder in wet processing routes for green body fabrication. Chemically, the crystallinity of the HA powder was found to be largely enhanced with the increase in calcination temperatures. In contrary, a high retardation in the carbonate ion content was found. Physically, all the powder properties in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 45 publications
6
16
0
Order By: Relevance
“…Increase in calcination temperature produced a narrow stretching band of adsorbed denoted by water wavelength 2357.01cm-1. The results were in agreement with Ahmed et al [26] which reported adsorbed water becomes narrower under the treatment of heat. Another significant peak attributed to CO3 2also found at wavelength 1409.96 cm -1 and 1186.22 cm -1 .…”
Section: Morphology and Structure Of Hydroxyapatitesupporting
confidence: 92%
See 1 more Smart Citation
“…Increase in calcination temperature produced a narrow stretching band of adsorbed denoted by water wavelength 2357.01cm-1. The results were in agreement with Ahmed et al [26] which reported adsorbed water becomes narrower under the treatment of heat. Another significant peak attributed to CO3 2also found at wavelength 1409.96 cm -1 and 1186.22 cm -1 .…”
Section: Morphology and Structure Of Hydroxyapatitesupporting
confidence: 92%
“…The absorption band is observed at wavelength 2360.87cm -1 attributed to stretching band confirmed presence of OH -. An earlier report by Ahmed et al [26], has mention presence of OHin the sample of hydroxyapatite when sintered at 900 o C. Fig.2 (e) represent FSHAp-1000 display by broad-spectrum contains functional group attribute to OHwith ion stretching mode ranging from wavelength 3400 cm -1 which engaged in amorphous solid. Asymmetric stretching of CO3 2is observed at wavelength 1406.11 cm -1 while the asymmetric stretching mode belongs to PO4 2at wavelength was detected at wavelength 1012.63 cm -1 .…”
Section: Morphology and Structure Of Hydroxyapatitementioning
confidence: 80%
“…The presence of broad peaks reveals the occurrence of smaller-sized particles, compared to samples prepared without SA. 30 The presence of SA in the precipitation of HAP has a strong inuence in the particle size. The average crystallite size of the HAP samples calculated using Debye-Scherrer's equation is given in Table 1.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Spray dried granules presented the highest degree of SSA and total pore volume. The heat treatment decreased the SSA and total pore volume due to growth and necking of HA nanoparticles during the sintering process . The SSA and total pore volume of the SD‐HA and SD‐8SrHA decreased sharply to the lower degrees after the heat treatment at 1000°C.…”
Section: Resultsmentioning
confidence: 99%